Minimum Audible Angle in 3rd-Order Ambisonics in Horizontal Plane for Different Ambisonic Decoders - Katarzyna Sochaczewska; Karolina Prawda; Paweł Małecki; Magdalena Piotrowska; Jerzy Wiciak (Applied Sciences)
As immersive audio is gaining popularity, the perceptual aspects of spatial sound reproduction become relevant. The authors investigate a measure related to spatial resolution, the Minimum Audible Angle (MAA), which is understudied in the context of Ambisonics. This study examines MAA thresholds in the horizontal plane in three ambisonic decoders—the Sample Ambisonic Decoder (SAD), Energy-Preserving Ambisonic Decoder (EPAD), and All-Round Ambisonic Decoder (AllRAD). The results demonstrate that the decoder type influences spatial resolution, with the EPAD exhibiting superior performance in MAA thresholds (<semantics>1.24∘</semantics> at <semantics>0∘</semantics> azimuth) compared to the SAD and AllRAD. These differences reflect the discrepancies in the decoders’ energy vector distribution and angular error. The MAA values remain consistent between decoders up to <semantics>30∘</semantics> azimuth but diverge significantly beyond this range, especially in the <semantics>60∘</semantics>–<semantics>135∘</semantics> region corresponding to the cone of confusion. The findings of this study provide valuable insights for spatial audio applications based on ambisonic technology.